Segment coordination and variability among prospectively injured and uninjured runners - Desai, G. A.; Gruber, A. H. (Journal of Sports Sciences, 2020)
Coordinative variability (CAV) and underlying coordinative patterns are potential running-related overuse injury (RROI) mechanisms, but prospective analyses are needed. This study compared lower limb CAV and coordinative patterns between prospectively injured and uninjured runners. Knee, shank, and ankle kinematics were collected for 39 recreational runners at the beginning of a 6-month follow-up period. Subjects were classified as injured (n=21) or controls (n=18) based on RROI incidence during follow-up. CAV was quantified using modified vector coding. Time spent in each coordinative pattern category was quantified using binning frequency analysis. Coordinative patterns were classified as mechanically unsound if underlying joint/segment motions opposed anatomically allowable running motion. Wilcoxon Rank-Sum tests compared CAV and binning frequencies between groups within different stance portions for knee-shank, shank-ankle, and knee-ankle couplings (a=0.05). During initial-stance, the injured group displayed significantly greater knee-ankle CAV (effect size (ES)=1.1), knee-shank CAV (ES=0.97), and greater frequency of mechanically unsound knee-shank (ES=0.72) and shank-ankle (ES=0.63) motion. During mid-stance, the injured group displayed lower frequency of mechanically sound knee-ankle motion (ES=0.31). In late-stance, the injured group displayed greater shank-ankle CAV (ES=0.11). Mechanically unsound coordinative patterns along with greater knee-ankle and shank-ankle CAV potentially lead to RROI.